2022
DOI: 10.5752/p.2316-9451.2022v10n2p26-56
|View full text |Cite
|
Sign up to set email alerts
|

Design Sensível a Valores na Computação: um Mapeamento Sistemático de Literatura

Abstract: O design sensível a valores (DSV) é uma proposta que conecta valores humanos a novos produtos, o que  pode trazer grandes contribuições para o desenvolvimento de novas tecnologias. Para compreender o uso do design sensível a valores, benefícios e contribuições para a computação, este artigo tem como objetivo apresentar os resultados de um mapeamento sistemático da literatura, fazendo um levantamento de artigos publicados a partir de 2010, e disponíveis nas bibliotecas digitais ACM Digital Library, IEEE Xplore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…VSD emerged in the 1990s when it was identified that, in developing new technologies, the predominant focus of developers was the functionality of the application, primarily concerned with usability, reliability, etc. (Oliveira and Ishitani, 2022). This critique is also raised by Feminist HCI, which considers the focus on objectifying usability, as it is more concentrated on time and errors in task performance than on agency, personal goals, and the individual's life vision (Bardzell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…VSD emerged in the 1990s when it was identified that, in developing new technologies, the predominant focus of developers was the functionality of the application, primarily concerned with usability, reliability, etc. (Oliveira and Ishitani, 2022). This critique is also raised by Feminist HCI, which considers the focus on objectifying usability, as it is more concentrated on time and errors in task performance than on agency, personal goals, and the individual's life vision (Bardzell, 2010).…”
Section: Introductionmentioning
confidence: 99%